Stigma Related to Tuberculosis Among Patients Attending DOTS Clinics of Dharan Municipality - Aryal, S; Badhu, A; Pandey, S; Bhandari, A; Khatiwoda, P; Khatiwada, P; Giri, A (Kathmandu University Medical Journal, 2012)
Background The patients suffering from tuberculosis are receiving shame and unfair treatment from the people living around them within their own society attending DOTS clinic of Dharan municipality. Objective To assess the stigma experienced by tuberculosis patients and to find out the association between stigma experienced by Tuberculosis patient and the selected variables (socio-demographic characteristics, clinical profile and illness experience). Methods Descriptive Cross Sectional study was done among sixty tuberculosis patients. Stratified random sampling was used to select the main center and sub center of Tuberculosis treatment and population proportionate simple random sampling using lottery method was done. Data was collected using predesigned, pretested performa from Explanatory Model Interview Catalogue developed by World Health Organization. Results The study revealed that 63.3% of the subjects were stigmatized. There was association between stigma and variables such as occupation, monthly family income and past history of Tuberculosis. There was also association of stigma with treatment phase, category of the patient and past outcome of illness. Conclusion Due to lack of knowledge and awareness about Tuberculosis, many patients were stigmatized. Efforts should be made to educate the public about Tuberculosis to reduce stigma experienced by Tuberculosis patients and improve the compliance of the patient. KATHMANDU UNIVERSITY MEDICAL JOURNAL  VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 48-52 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6914